ANALISIS PERBANDINGAN ALGORITMA C4.5 DAN ID3 UNTUK FAKTOR KEPUASAN KONSUMEN WARUNG ICHA STEAK & SEAFOOD - Muhammad Farhan Arief; Herry wahyono; Nuke Chusna (TEKNOKRIS, 2022)
Warung Icha Steak & Seafood is an MSME type food stall business that focuses on the culinary field that sells food in the form of steak and processed food from the sea. Efforts to retain consumers are certainly not an easy thing, especially the thing that is now being faced by Icha Steak & Seafood stalls is declining the number of consumers and customers. This is a threat that is being faced by the msme because it will have an impact on revenue turnover. The purpose of this study is to find out what factors need to be improved to achieve consumer satisfaction of Warung Icha Steak & Seafood. Apply the Classification method with C4.5 and ID3 algorithms to group the most influential factors for consumer satisfaction. Perform a Comparison of both C4.5 and ID3 algorithms with the Cross Validation method. Itwas concluded that the problem of determining the consumer satisfaction factor of Warung Icha Steak & Seafood can be solved using data mining techniques, namely with the C4.5 and ID3 algorithms, resulting in the same decision tree and 6 rules and the most dominant factor is Service Friendliness (C8) with a gain value of 0.41370089. Testing the ID3 algorithm has a high level of accuracy of 98.50%, a Precision value of 98.77% and a Recall value of 99.38%